2021
DOI: 10.1186/s13567-021-00958-2
|View full text |Cite
|
Sign up to set email alerts
|

Lawsonia intracellularis infected enterocytes lack sucrase-isomaltase which contributes to reduced pig digestive capacity

Abstract: Lawsonia intracellularis is endemic to swine herds worldwide, however much is still unknown regarding its impact on intestinal function. Thus, this study aimed to characterize the impact of L. intracellularis on digestive function, and how vaccination mitigates these impacts. Thirty-six L. intracellularis negative barrows were assigned to treatment groups (n  =  12/trt): (1) nonvaccinated, L. intracellularis negative (NC); (2) nonvaccinated, L intracellularis challenged (PC); and (3) L. intracellularis challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Similar to F. nucleatum, Bacteroides, and B. fragilis also have been implicated in colorectal cancer, in which certain strains have been found to be capable of promoting cellular proliferation by stimulation of Wnt signaling. The latter is a signaling pathway that has also been described to be altered in pigs with PPE (4,(34)(35)(36). Increased abundance of Bacteroides has also been found in the fecal microbiome of pigs challenged with a pure culture of L. intracellularis and to be negatively associated with weight gain in swine (8, 10).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to F. nucleatum, Bacteroides, and B. fragilis also have been implicated in colorectal cancer, in which certain strains have been found to be capable of promoting cellular proliferation by stimulation of Wnt signaling. The latter is a signaling pathway that has also been described to be altered in pigs with PPE (4,(34)(35)(36). Increased abundance of Bacteroides has also been found in the fecal microbiome of pigs challenged with a pure culture of L. intracellularis and to be negatively associated with weight gain in swine (8, 10).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has been shown that LI -challenged pigs had lower ileal sucrase activity [ 30 ]. Helm et al also found that LI -infected enterocytes lack sucrase-isomaltase, contributing to reduced pig digestive capacity [ 32 ]. Bile acids and vitamin B 12 were nutrients absorbed primarily in the ileum, which played an important role in maintaining metabolic homeostasis and regulation [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another strategy against LI infection is vaccination. A live attenuated vaccine against LI was developed and induced immunity against wild type of LI and improvement of host clinical signs as well as higher productivity was observed [3,4]. Besides the clinical onset of proliferative enteropathy, subclinical LI infection also damaged the host intestine and loss of productivity was present [5].…”
Section: Introductionmentioning
confidence: 99%